IMMU-22. EARLY RELEASE OF TYPE I INTERFERON DRIVES BRAIN CANCER IMMUNOGENICITY AND RESPONSE TO IMMUNOTHERAPY. (9th November 2020) - Wummer, Brandon; Qdaisat, Sadeem; Grippin, Adam; Karachi, Aida; Weidert, Frances; Huang, Jianping; Rahman, Maryam; Mitchell, Duane; Mendez-Gomez, Hector; Sayour, Elias
Abstract: BACKGROUND: Molecular drivers of cancer immunogenicity in brain tumors are still being unraveled. While BATF3 expression, STING, and interferon response factors (IRFs) are necessary for cancer immunogenicity, the presence of type I interferon (IFN-I) is contextual having been reported to elicit both anti-tumoral and pro-tumoral effects. A better understanding of IFN-I signaling mechanisms is necessary to elucidate drivers of brain cancer immunogenicity and resistance. OBJECTIVE: We sought to assess the role of IFN-I signaling in brain tumor immunogenicity and response to immune checkpoint inhibitors (ICIs) in ICI sensitive brain tumor models (i.e. GL261). We then sought to develop strategies to reset IFN-I signaling in ICI resistant brain tumor models (i.e. KR158b). METHODS: To reset IFN-I signaling in immunologically 'cold' tumors unresponsive to ICIs, we developed lipid-nanoparticles (NPs) to deliver mRNA payloads to the brain tumor microenvironment (TME). RESULTS: In immune-sensitive GL261 tumors, we showed that early release of IFN-I unlocks cancer immunogenicity and ICI response. Blockade of IFN-I during tumorigenesis (within 24h, but not days later) increases tumorigenicity and abrogates ICI activity in sensitive tumors. In ICI resistant KR158b tumors, we show that systemic administration of tumor-derived RNA-NPs localize to myeloid cells within the TME for simultaneous activation of multiple innate pathways including BATF3 (necessary for effector DCs), IRF5 (necessary for M2 to M1 macrophage reprograming), and IRF7 (necessary for IFN-I production). These RNA-NPs induce near-immediate release of IFN-I (within hours), reprogram the brain TME in an IFNAR1 (IFN-I receptor) dependent manner, and elicit significant anti-KR158b efficacy as a monotherapy. Following IFNAR1 blockade, RNA-NP mediated anti-tumor efficacy was abrogated. We demonstrated safety of tumor-specific RNA-NPs (derived from KR158b) in acute/chronic GLP toxicity studies without normal-brain cross-reactivity, and confirmed feasibility/safety and immunologic activity in large-animal studies. FUTURE DIRECTIONS: We have since received FDA-IND approval for first-in-human trials (IND#BB-19304) in glioblastoma patients.